International academic mobility in the perception of students of English - Carranza de Mendoza, Martha Patricia (Universidad Autónoma de Tamaulipas, 2018)
In 2013, the Foro Bilateral sobre Educación Superior, Innovación e Investigación (FOBESII) was created with the objective of promoting cooperation and understanding between the United States of America (USA) and Mexico. The strategy proposed to promote academic mobility through the Proyecta 100 000 program which was established for the period of 2014 to 2018. This work examines the perceptions of students who participated in the program. An exploratory study was performed with the participation of 10 students of a polytechnic university located in northeast Mexico. Data were collected with the use of qualitative interviews. Results indicated that the students’ perceptions focused on three aspects of the program: (1) the teaching quality at the host university; (2) internationalization; and (3) administrative issues and delivery of financial support. Findings indicate that, the course taken during the program helped the students develop their English language competence partially. The stay in a different country and the time spent with students of other nationalities raised wareness to other cultures. The delay in the delivery of financial resources affected the credibility of the program.